Model comparison and performance analysis of multi-frequency precise positioning with the joint BDS-2 and BDS-3 system. Issue 8 (15th April 2022) - Deng, Chenlong; Qi, Shufeng; Tang, Weiming; Hui, Mengtang; Zou, Xuan; Wang, Yawei; Li, Yangyang; Guo, Chi
Abstract: The global BeiDou Navigation Satellite System (BDS-3) has been formally operated together with the regional system (BDS-2) for more than one year. However, the different frequency numbers between BDS-2 and BDS-3 makes their integration a troublesome problem, especially when all available frequencies are taken into account. To make a comprehensive analysis of multi-frequency precise positioning models in BDS-2 and BDS-3, the popular real-time kinematic positioning is taken as an example for data processing. Since in general the reliable, successful and rapid ambiguity resolution is the key of an appropriate multi-frequency positioning model, the framework of multi-frequency ambiguity resolution (AR) is summarized first. The usual loose combined model for the joint BDS-2 and BDS-3 system is described. To make full use of the common frequencies B1I and B3I in BDS-2 and BDS-3, an improved combined model is proposed where both the loose combined mode and tightly combined mode are applied. The performance of ambiguity resolution (AR) and positioning precision are obtained from four short baselines with different lengths in the above two models and with different elevation masks. The comparison results show that: (1) Both the combined model and improved combined model can achieve nearly 100% AR success rate and correctly-fixed rate, as well as consistent centimeter level's fixed solution; (2) The improved combined model can obtain higher AR fixed rate and shorter time to first fix (TTFF) compared with the usual combined model, and the improvements can be up to 15% for the fixed rate and 37% for TTFF; (3) To achieve the largest AR fixed rate while keep reliable AR and precise positioning, a relative large elevation mask such as 30° is highly recommended for a joint BDS-2 and BDS-3 system with sufficient observed satellites.